Evaluating Nonclinical Performance of the Academic Pathologist - Austin Blackburn Wiles MD; Michael O. Idowu MD, MPH; Charles V. Clevenger MD, PhD; Celeste N. Powers MD, PhD (Elsevier, 2018)
Academic pathologists perform clinical duties, as well as valuable nonclinical activities. Nonclinical activities may consist of research, teaching, and administrative management among many other important tasks. While clinical duties have many clear metrics to measure productivity, like the relative value units of Medicare reimbursement, nonclinical performance is often difficult to measure. Despite the difficulty of evaluating nonclinical activities, nonclinical productivity is used to determine promotion, funding, and inform professional evaluations of performance. In order to better evaluate the important nonclinical performance of academic pathologists, we present an evaluation system for leadership use. This system uses a Microsoft Excel workbook to provide academic pathologist respondents and reviewing leadership a transparent, easy-to-complete system that is both flexible and scalable. This system provides real-time feedback to academic pathologist respondents and a clear executive summary that allows for focused guidance of the respondent. This system may be adapted to fit practices of varying size, measure performance differently based on years of experience, and can work with many different institutional values.